Agricultural extension in Eastern Democratic Republic of Congo: Does gender matter? - Lambrecht, Isabel B.; Vanlauwe, Bernard; Maertens, Miet (Oxford University Press, 2016)
Agricultural extension programmes often evaluate their gender strategy by the proportion of female participants. However, female participation is not necessarily conducive for reaching programme objectives. We analyse whether participation of female farmers in an agricultural extension programme in South-Kivu increases adoption of three technologies: improved legume varieties, row planting and mineral fertiliser. Joint male and female programme participation leads to the highest adoption rates. Female participation is not conducive for the adoption of capital-intensive technologies while it is for (female) labour-intensive technologies. Participation of female-headed households is more effective for technology adoption than participation of female farmers in male-headed households.